Specialization courses: new university target - Vasconcelos, Rosa (2011)
The implementation of the Bologna Process in the Portuguese Higher Education system led to deep changes at this education level. In order to harmonize and to level the Portuguese higher education with other European countries several measures were determined, including access expansion, especially for new target groups. Among others the +23 year olds students and Technology Specialization Courses (CET) are considered new target groups. CET´s Students quota are new at this level of education, so a study was carried out to understand the evolution of these new target group courses in Engineering and Technology, at University of Minho. For such, a data survey of students that entered through this quota was used and their academic path analyzed. These students have expectations, motivations and different backgrounds in comparison with other students. Understand their performance in higher education may help to answer adequately to the needs of this new target group.